2019
DOI: 10.1186/s12911-019-0764-5
|View full text |Cite
|
Sign up to set email alerts
|

Relation path feature embedding based convolutional neural network method for drug discovery

Abstract: Background Drug development is an expensive and time-consuming process. Literature-based discovery has played a critical role in drug development and may be a supplementary method to help scientists speed up the discovery of drugs. Methods Here, we propose a relation path features embedding based convolutional neural network model with attention mechanism for drug discovery from literature, which we denote as PACNN. First, we use predications from biomedical abstracts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The health hazards that ADEs may pose to individuals motivate the extensive work on the application of various computational methods for pharmacovigilance. Authors of this study have either used an open LBD [ 15 , 23 , 24 ] or a closed LBD [ 22 , 25 ] approach for the detection of drug/ADE pairs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The health hazards that ADEs may pose to individuals motivate the extensive work on the application of various computational methods for pharmacovigilance. Authors of this study have either used an open LBD [ 15 , 23 , 24 ] or a closed LBD [ 22 , 25 ] approach for the detection of drug/ADE pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Ranking of LBD-generated hypotheses have been performed by Zhang et al [ 27 ] through a machine learning-based filter (lasso regression filter) and Rastegar-Mojarad et al [ 21 ] by using a binary classifier. Machine learning algorithms like logistic regression [ 22 , 23 , 29 ] and k-Nearest Neighbor (kNN) [ 29 ] have been incorporated in models proposed by authors in this review. Rather et al [ 40 ] integrated Word2vec, a neural network based algorithm, in their LBD approach and showed that the model was able to retrieve strong relationships which were not identified by UMLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various specially designed AI/ML models have been proposed for detecting novel drug indications. Here, we classify the ML applications for drug repositioning into the following three categories: (i) Similarity‐based methods that employ different types of classifiers like logistic regression, 305,306 SVM, 307–309 RF, 310,311 KNN, 312 and CNN, 313 (ii) feature vector‐based methods that utilize supervised 314–318 and semisupervised 319–321 learning algorithms, and (iii) network‐based methods that mainly use semisupervised learning algorithms (e.g., Laplacian regularized least square, 322–324 label propagation, 325 random walk, 326 and RF 310 ). We provide an in‐depth discussion of these three classes of AI‐based drug repositioning applications in the Supporting Information.…”
Section: Ai/ml Applications In Drug Discoverymentioning
confidence: 99%
“…The current tasks of biomedical relation extraction mainly focus on the extraction of binary relations in single sentences, such as protein-protein interaction (PPI), chemical-protein interaction (CPI) and drug-drug interaction (DDI) [ 1 – 3 ]. It is crucial for biomedical relation extraction to automatically construct a knowledge graph, which supports a variety of downstream natural language processing (NLP) tasks such as drug discovery [ 4 ]. An obvious problem is that as the biomedical literature continues to grow, there is a large number of biomedical entities whose binary relations exist not only in a single sentence but also in cross-sentences.…”
Section: Introductionmentioning
confidence: 99%